Then (x+y)^n-z^n = x^n+y^n-z^n + [] = []

where [] is the 'innards' of (x+y)^n

However every term in [] contains at least an xy component.

x+y=Z is greater than z, and [] doesn't change regardless of how we assign x

and y.

So let x=z, and we have a contradiction:

(x+y)^n-z^n will not be divisible by z unless y=kz, k>0.

Jon Perry

perry@...

http://www.users.globalnet.co.uk/~perry/maths/

http://www.users.globalnet.co.uk/~perry/DIVMenu/

BrainBench MVP for HTML and JavaScript

http://www.brainbench.com